The Impact of Integrity, Professionalism, and Self-Efficacy of Auditors on Audit Quality - Kenny Ardillah; Rebecca Angelina (JRB-Jurnal Riset Bisnis, 2021)
Audit quality is a finding of violations by the auditor in recording the client's financial statements. Audit quality is strongly influenced by the auditor as the party auditing the financial statements, so the auditor needs to follow and carry out his duties by the auditing standards that apply during the audit process. This investigation expects to analyze the impact of integrity, professionalism, and self-efficacy of auditors on audit quality. The populace in this investigation were all autonomous auditors who work in Public Accounting Firm which are enlisted with the Republic of Indonesia's Financial Audit institution. The sampling technique used in this study was simple random sampling. Data collection techniques in this study using library research and questionnaires. Hypothesis testing in this study uses multiple regression data analysis techniques using SPSS version 25.0. The results of this study indicate that integrity, professionalism, and self-efficacy have a positive effect on audit quality. The implications of this research are academic implications to determine the factors that can affect audit quality and can be used as material for developing research and knowledge, especially in the field of accounting related to audit quality and practical implications for developing further research in the auditing field.